Stable N,N’-diarylated dihydrodiazaacene radical cations - Xie, Gaozhan; Bojanowski, Maximilian; Brosius, Victor; Wiesner, Thomas; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2021)
Three stable N,N’-diarylated dihydroazaacene radical cations were prepared by oxidation of neutral N,N’-diarylated dihydroazaacenes synthesized via palladium-catalyzed Buchwald-Hartwig aminations of aryl iodides with N,N’-dihydroazaacenes. Both neutral as well as oxidized species were investigated via UV-vis spectroscopy, single crystal analysis, and DFT calculations. All the radical cations are surprisingly stable—their absorption spectra in dichloromethane remain unchanged in ambient conditions for at least 24 hours.
First published: 30 December 2020
Gesehen am 18.09.2021